Academic pay loadings and gender in Australian universities. (November 2016) - Bailey, Janis; Peetz, David; Strachan, Glenda; Whitehouse, Gillian; Broadbent, Kaye
Academic pay loadings are one potential mechanism of gender pay disparity in universities. Drawing on a large-scale survey of Australian academics with over 8000 respondents, we analyse how 'discretionary' and higher duties loadings (or bonuses) are distributed between men and women, and investigate the reasons for such distributions. Investigating both incidence and quantum, we find that discretionary loadings are particularly susceptible to gender influences. We explain this finding in terms of the concepts of regulation distance and the meritocracy paradox. The findings have implications for the design of loadings schemes in universities, and, by implication, in other kinds of organisations that provide loadings.